Phase-field study of the effect of stress field and fission rate on intragranular Xe bubble evolution in U3Si2 nuclear fuel - Ma, Cong; Liu, Caiyan; Zhao, Min; Xin, Tianyuan; Wu, Lu; Pan, Rongjian; Qin, Jiantao; Zhang, Jing (Frontiers in Energy Research, 2023)
Due to the superior thermal conductivity and high uranium density, U3Si2 is an excellent candidate for conventional UO2 nuclear fuel and shows great potential application in accident-tolerant fuel (ATF) assembly of light water reactors (LWR). Currently, the behavior of Xe bubbles with internal or applied stress is rarely investigated, restricting further understanding of swelling in U3Si2. The mesoscopic phase field method has been developed in this work to study the spatial and temporal Xe bubble evolution in U3Si2. The results show that the bubble density and its average size increase as the fission rate increases. Applied stress accelerates the nucleation and growth of gas bubbles, reshaping the bubbles’ morphology from spherical in a stress-free state into elongated along the applied direction in a stressed state. The gas bubbles in a local dislocation stress field nucleate preferentially at stress-concentrated sites and spread over the whole system in succession, and the bubble coarsening is controlled by the stress overlap of the dislocation pair. The results show a practical phase field method for Xe bubble evolution study in U3Si2, which can be expanded into swelling behavior investigation in other fuels and lay a solid foundation for the development of ATF assembly.